Market, Planning, Morality - Rybakovienė, Vanzeta (Problemos, 1995)
In the present economical reality on can see a conflict between administrative and market approaches. The first is linked to collective morality, the second to individualistic one. The paper deals with the principles of both moralities. The economical as well as historical premises of the principles are clarified up. The conclusion is drawn that the attempt to oppose market economy as “immoral” to “socialist economy” as highly moral has no grounds.